2011
DOI: 10.1103/physrevb.83.115424
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of the implantation of low-energy boron and nitrogen ions into graphene

Abstract: By combining classical molecular dynamics simulations and density functional theory total energy calculations, we study the possibility of doping graphene with B/N atoms using low-energy ion irradiation. Our simulations show that the optimum irradiation energy is 50 eV with substitution probabilities of 55% for N and 40% for B. We further estimate probabilities for different defect configurations to appear under B/N ion irradiation. We analyze the processes responsible for defect production and report an effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
126
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 54 publications
7
126
0
Order By: Relevance
“…Therefore, previous theoretical findings are confirmed which show that in the energy range studied the indeed create only single or double vacancy defects. 18 Only significantly lower energies <200 eV or >50 keV would lead to other effects like C atom substitution / ion implantation 28 and graphene amorphization events in the vicinity of the impact position, 18 respectively. Furthermore, the nature of the experimental design and the simplified modeling blur the effects of precise impact position on the C atom removal rate but gives a statistical average over all possible positions therefore corresponds to the realistic situation during graphene etching by energetic ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, previous theoretical findings are confirmed which show that in the energy range studied the indeed create only single or double vacancy defects. 18 Only significantly lower energies <200 eV or >50 keV would lead to other effects like C atom substitution / ion implantation 28 and graphene amorphization events in the vicinity of the impact position, 18 respectively. Furthermore, the nature of the experimental design and the simplified modeling blur the effects of precise impact position on the C atom removal rate but gives a statistical average over all possible positions therefore corresponds to the realistic situation during graphene etching by energetic ions.…”
Section: Resultsmentioning
confidence: 99%
“…More insight about the interaction has been obtained by a few theoretical investigations using Monte Carlo simulation. 17,18,28 Despite a growing understanding of the 2D sputtering mechanism including graphene amorphization upon Ga + irradiation, 29 there is few report of combined experimental and theoretical investigation about the fate of freestanding graphene layers subject to ion bombardment of various ion species and energies, hampering exploitation of the advanced manufacturing capability of the ion bombardment on freestanding graphene.…”
mentioning
confidence: 99%
“…Earlier theoretical predictions on B and N implantation 35 also suggest the possibility of implanting atoms into graphene, and in a recent experiment B and N atoms were, in fact, implanted in free-standing graphene 13 at a landing energy of 20 eV. Individual carbon adatoms are predicted to be mobile at room temperature, 23,25 and are thus not expected to be found after deposition, although, upon encountering another carbon adatom, a highly stable self-interstitial dimer can be formed.…”
mentioning
confidence: 97%
“…[25][26][27] In a bid to produce uniformly6doped single6 layer graphene specimens, the successful implementation of low6energy ion implantation with either N or B was recently demonstrated, [28][29][30] achieving retention levels of the order of ~1% in good agreement with theoretical predictions. 31 This ion6implantation technique, commonly used by the modern semiconductor industry for doping Si wafers, for instance, has the advantage of allowing the uniform incorporation over a large area of single dopants on a pre6screened, single6layer, suspended graphene sample, and of producing comparatively few defects or ad6atom configurations. 29 Recent progress in the application of Scanning Transmission Electron Microscopy (STEM) based spectroscopy to the study of 26dimensional materials has demonstrated the technique's ability to fingerprint single dopant atoms in graphene [32][33][34][35] and to differentiate between different electronic structure configurations, such as trivalent and tetravalent single atom Si impurities using subtle changes in the near edge fine structure of the Si L 2,3 ionisation edge in electron energy loss spectroscopy (EELS).…”
mentioning
confidence: 99%